Obesity and kidney disease: hidden consequences of the epidemic. Issue 1 (25th April 2017) - Kovesdy, Csaba P; Furth, Susan; Zoccali, Carmine; ,
Abstract : Obesity has become a worldwide epidemic, and its prevalence has been projected to grow by 40% in the next decade. This increasing prevalence has implications for the risk of diabetes, cardiovascular disease and also for chronic kidney disease. A high body mass index is one of the strongest risk factors for new-onset chronic kidney disease. In individuals affected by obesity, a compensatory hyperfiltration occurs to meet the heightened metabolic demands of the increased bodyweight. The increase in intraglomerular pressure can damage the kidneys and raise the risk of developing chronic kidney disease in the long term. The incidence of obesity-related glomerulopathy has increased tenfold in recent years. Obesity has also been shown to be a risk factor for nephrolithiasis, and for a number of malignancies including kidney cancer. This year World Kidney Day promotes education on the harmful consequences of obesity and its association with kidney disease, advocating a healthy lifestyle and health policy measures that makes preventive behaviours an affordable option.